Incidence of type 1 diabetes by socio‐demographic characteristics among South Australian children: Whole‐of‐population study. (15th September 2020) - Begum, Mumtaz; Chittleborough, Catherine; Pilkington, Rhiannon; Mittinty, Murthy; Lynch, John; Penno, Megan; Smithers, Lisa
Abstract : Aim: To describe and compare the incidence of type 1 diabetes (T1D) in South Australia by individual and area‐level socio‐economic characteristics among children aged ≤11 years. Methods: This is a whole‐of‐population, data linkage study ( n = 231 685) conducted in South Australia, and included children born from 2002 to 2013, hospitalisation followed from 2002 to 2014. The study used de‐identified, linked administrative hospitalisation, birth and perinatal data from the South Australian Early Childhood Data Project. Incidence was calculated by identifying T1D cases from T1D‐related hospitalisations using International Classification of Disease, 10th Revision, Australian Modification diagnosis codes (E10, E101–E109). Results: Overall, 333 children aged ≤11 years (173 boys) were identified as having T1D. The T1D incidence rate was 23.0 per 100 000 person‐years (95% confidence interval (CI): 20.7–25.7), with no sex difference. T1D incidence was higher among children whose mothers were Caucasian, private patients and whose parents were employed. For example, T1D incidence was 26.0 per 100 000 (95% CI: 22.8–29.5) among children with both parents employed, compared to 20.0 per 100 000 (95% CI: 12.3–30.6) among children with both parents unemployed. There was no clear gradient in the association between area‐level socio‐economic position and T1D, with highest incidence for the fourth quintile (26.5 per 100 000 (95% CI: 20.9–33.1)). The most advantaged area (19.4 per 100 000 (95% CI: 13.8–26.5)) had lower incidence than the most disadvantaged area (23.5 per 100 000 (95% CI: 18.9–28.9)). Conclusion: T1D incidence rates differed depending on the measures of socio‐economic characteristics. Individual‐level indicators showed higher incidence among more advantaged children; however, there was no clear area‐level socio‐economic patterning of T1D.